Effect of Acarbose, Sitagliptin and combination therapy on blood glucose, insulin, and incretin hormone concentrations in experimentally induced postprandial hyperglycemia of healthy cats. (June 2016) - Mori, Akihiro; Ueda, Kaori; Lee, Peter; Oda, Hitomi; Ishioka, Katsumi; Arai, Toshiro; Sako, Toshinori
Abstract: Acarbose (AC) and Sitagliptin (STGP) are oral hypoglycemic agents currently used either alone or in conjunction with human diabetic (Type 2) patients. AC has been used with diabetic cats, but not STGP thus far. Therefore, the objective of this study was to determine the potential use of AC or STGP alone and in combination for diabetic cats, by observing their effect on short-term post-prandial serum glucose, insulin, and incretin hormone (active glucagon-like peptide-1 (GLP-1) and total glucose dependent insulinotropic polypeptide (GIP)) concentrations in five healthy cats, following ingestion of a meal with maltose. All treatments tended ( p  < 0.10; 5–7.5% reduction) to reduce postprandial glucose area under the curve (AUC), with an accompanying significant reduction ( p  < 0.05, 35–45%) in postprandial insulin AUC as compared to no treatment. Meanwhile, a significant increase ( p  < 0.05) in postprandial active GLP-1 AUC was observed with STGP (100% higher) and combined treatment (130% greater), as compared to either AC or no treatment. Lastly, a significant reduction ( p  < 0.05) in postprandial total GIP AUC was observed with STGP (21% reduction) and combined treatment (7% reduction) as compared to control. Overall, AC, STGP, or combined treatment can significantly induce positive post-prandial changes to insulin and incretin hormone levels of healthy cats. Increasing active GLP-1 and reducing postprandial hyperglycemia appear to be the principal mechanisms of combined treatment. Considering the different, but complementary mechanisms of action by which AC and STGP induce lower glucose and insulin levels, combination therapy with both these agents offers great potential for treating diabetic cats in the future. Highlights: The effect of Acarbose, Sitagliptin and their combination on postprandial blood parameter in healthy cats was studied. All treatments induced reductions to postprandial glucose and insulin area under the curve (AUC) values. Sitagliptin and combined therapy increased postprandial active GLP-1 AUC values. Sitagliptin and combined therapy reduced postprandial total GIP AUC values. Acarbose, Sitagliptin, and combination therapy especially, has great potential for treating diabetic cats.